Robot-asisted walking vs overground walking in stroke patients: An evaluation of muscle activity - Coenen, Pieter; Van Werven, G.; Van Nunen, M.; Van Dieën, J.; Gerrits, K.; Janssen, T. (2012)
Objective: There is increasing evidence that robot-assisted treadmill training might be useful for gait rehabilitation after stroke. The aim of this study was to evaluate the muscle activity of stroke patients during robot-assisted walking and overground walking, and of a group of able-bodied subjects during overground walking. Design: Case-control observational study. Subjects: Ten stroke subjects and 10 able-bodied control subjects. Methods: Electromyography measurements of 7 lower-limb muscles were made in 3 trials: robotic walking, in which stroke subjects walked in a robot-assisted gait orthosis; overground walking for the same group of stroke subjects; and overground walking for control subjects. Trials were compared with respect to electromyography amplitude of selected leg muscles. Results: Higher muscle activity during overground walking compared with robotic walking was found in several muscles during several phases of the gait cycle. A significant trial × leg interaction revealed smaller differences in muscle activity between the paretic and non-paretic leg during robotic walking compared with overground walking. Furthermore, the muscle activity pattern was not significantly different between control walking and robotic walking, while it was different between control walking and overground walking. Conclusion: Despite lower muscle activity, robot-assisted treadmill training may elicit a more symmetrical pattern of leg muscle activity, which approaches that of able-bodied individuals. © 2012 Foundation of Rehabilitation Information.